Clear speech - Gilbert, Judy B. (Cambridge University Press, 1993)
Pronunciation and Listening Comprehension in North American English. This is a revised and expanded version of the highly successful and innovative pronunciation text for intermediate to high-intermediate students of North American English. The Clear Speech, Third Edition, Student's Book provides learners with visual representations of important pronunciation features, such as voicing and syllable length. It features a reordered table of contents, a greater emphasis on listening recognition, and more coverage of vowel sounds. It also contains a Student Audio CD, so students can practice many of the exercises on their own.